Picolinic Acid in Patients with Chronic Hepatitis C Infection: A Preliminary Report - Jolanta Zuwała-Jagiello; Monika Pazgan-Simon; Krzysztof Simon; Maria Warwas (Mediators of Inflammation)
Macrophage activation seems to be a feature of chronic liver diseases. Picolinic acid (PA) as a macrophage secondary signal causes the activation of interferon-gamma- (IFN-γ-) prime macrophage and triggers cytokine-driven inflammatory reactions. The rationale for seeking increased PA formation in chronic viral hepatitis is based on the involvement of activated macrophages in chronic viral hepatitis-associated inflammation. The aim of this study was to determine serum PA levels in patients with chronic hepatitis C infection, taking into account the presence of diabetes. We assessed PA and high-sensitivity C-reactive protein (hsCRP) as a marker of inflammation in 51 patients with chronic hepatitis C infection (CHC), both with and without diabetes and 40 controls. Compared with the controls, the patients with CHC showed a significant increase in plasma concentrations of PA and hsCRP (P<0.01 and P<0.05, resp.). The values of PA and hsCRP were more elevated in patients with diabetes than without diabetes (both P<0.01). The positive relationships were between PA and hsCRP levels (P<0.05) and the presence of diabetes (P<0.001). We documented that significant elevation in serum PA levels is associated with diabetes prevalence and increased inflammatory response reflected in hsCRP levels in CHC patients.